Formulation Design of Orally Disintegrating Film Using Two Cellulose Derivatives as a Blend Polymer - Yoshiko Takeuchi; Fumika Hayakawa; Hirofumi Takeuchi (Pharmaceutics)
Background/Objectives: Orally disintegrating film (ODF) is prepared using water-soluble polymers as film-forming agents. To improve mechanical and disintegration properties, some polymers need to be blended with others. This study aimed to investigate the utility of hydroxypropyl cellulose (HPC) and hydroxypropyl methyl cellulose (HPMC) as blend film-forming components for ODFs. Methods: Placebo ODFs were prepared using polymer mixtures with blend ratios ranging from 20% to 80% HPC with HPMC. Mechanical properties, including tensile strength, elastic modulus, elongation at break, and folding endurance, as well as disintegration times, were evaluated. Additionally, blend films incorporating donepezil hydrochloride (DH) as a model active pharmaceutical ingredient (API) were prepared and assessed to determine their mechanical properties and disintegration behavior. Results: Blend films were successfully formed using HPMC/HPC solutions. The 40/60 and 20/80 HPMC/HPC blends exhibited the lowest mechanical strength and elongation, whereas blends containing more than 40% HPC demonstrated shorter disintegration times. Films with DH were successfully formed, though the addition of DH reduced tensile strength and elongation. The decline in mechanical properties was mitigated in HPMC/HPC blend films. Our results, including DSC and FTIR results, led us to conclude that the HPMC/HPC blend films were micro-immiscible, but they were macro-miscible when the amount of the minor component was sufficiently small. Conclusions: HPMC/HPC blends in appropriate ratios are effective as film-forming polymers for ODFs. The addition of DH impacts the mechanical properties, but the decline is less pronounced when using HPMC/HPC blends.